A portal to transnational communication: problematizing identity politics in Ha Jin's A Map of Betrayal. Issue 10 (2nd October 2020) - Chen, Chung-jen
ABSTRACT: Based on the real story of Larry Wu-Tai Chin, the alleged spy who purloined information while working for the CIA and sold classified documents to China, A Map of Betrayal problematises the monophonic dominance of keywords of national identity. As the two interspersing narratives of the spy Gary and his daughter Lilian complicate the double life of a spy and an immigrant, this novel investigates the contradictions of patriotism as religion or rationality, citizenship as empowerment or restriction, and the motherland as the initiating point of entrenchment or activism. At the core of the paradox is a challenge to the possibility of transnational and transcultural communication between China and the United States. This paper reads the duality of loyalty and betrayal that encapsulates the US–China relationship in the heat of the Cold War. While A Map of Betrayal functions as a proxy to reflect the Sino-American relationship during and after the Cold War, discussions of identity politics would be incomplete without examining the mobility of transnationality and the flexibility of belonging in their rightful position at the gateway between two countries. Gary and Lilian's positions as portals that facilitate transcultural and transnational communication are not only essential to inquiries into loyalty, citizenship and patriotism, but are also helpful in clarifying similar concerns in Asian-American studies.